Zmanjšana zmožnost samostojnega in varnega hranjenja - pogosta težava v rehabilitacijski zdravstveni negi - Vidmar, Veronika (Rehabilitacija (Ljubljana), 2014)
Background: Nurses usually identify feeding as one of the most common problems of patients that they take care for. The aim of this study was to determine how much assistance is needed by the patients who are admitted to the University Rehabilitation Institute in Ljubljana, Slovenia (URI). We included the patients admitted to the Department for rehabilitation after cerebrovascular stroke (Dept. 2) and at the Department for rehabilitation of patients after traumatic brain injury, with multiple sclerosis and other neuromuscular diseases (Dept. 1). We wanted to find out how often the patients have swallowing problems that increase the risk for choking, how often they need a nasogastric tube, and what is the extent of nutritional risk. Methods: The patients admitted to the abovementioned two departments of the URI between 1 March and 31 August 2013 were included in the study. We examined all the medical and nursing records, records of the assessment of nutritional risk to the patient (NRS 2002) and results at motor subscale of the Functional Independence Measure (FIM). Results: A total of 334 patients were included in the study, 140 from the Dept. 2 and 194 from the Dept. 1. We found that 73.5 % of the patients had feeding problems when they were admitted to inpatient rehabilitation and 61.3% at discharge. Swallowing problems that increased the risk for choking were observed in 29% of the patients; 4% of the patients had a nasogastric tube and 10% of the patients needed an individual food plan because of the established nutritional risk. Conclusion: Feeding the patients is one of the most frequent problems we are dealing with in our rehabilitation institute. Therefore, our nurses need a lot of knowledge, time and patience when they feed such patients.
Keywords: feeding; health care; hranjenje; motnje požiranja; Nursing; rehabilitacija; Rehabilitation; swallowing disorders; vocational rehabilitation; zdravstvena nega